Determinación de otoacariasis canina mediante diagnóstico de laboratorio por hisopados óticos en la ciudad de Machala - Madrid Cartuche, María José (2012)
In the city of Machala, Ecuador, took place an otocariasis research diagnosed by the the Otic Swab method. The objectives were: 1. To determine the rate of canine Otocariasis at the clinical level in the city of Machala. 2. Stablish the presence of Otocariasis according to the age and the ear's shape (the breed). 120 cases were taken with affected ears. The case studies were given a test using a microscope which was done as follows: using a cotton swab soaked in glycerin, enough sample was collected from the ear and was placed on a slide, making small circular movements. Finishing this process, another slide was placed on the sample to finally be taken to the microscope where it was observed with a 40 x lense. This way it was determined the appearance, or absence of mites. In the animals examined, a high presence of positive cases was found, which was a total of 53. This indicates that canines in this "cantón" are more prone to be affected by this illness because of the parasite being highly contagious. Statistically Factors Age and type of ear, did not significantly influence the prevalence of canine Otoacariasis Machala City.